Comment: Introducing Neurologic Diagnostics in 2035. (9th November 2021) - Jones, Lyell K.; Gross, Robert A.
Abstract : When you imagine the state of neurologic diagnostics in 2035, what do you see? Most of us expect to see continued developments in technology, but how will this progress affect patient care and the practice of neurology? Will neurologic diagnosticians be replaced by a dystopian hodgepodge of multi-omic assays, advanced machine learning algorithms, and handheld Star Trek tricorders?